Desarrollo del proceso de atención en enfermería en paciente de 45 años de edad, con sindrome compartimental en miembro superior izquierdo - Sánchez Hidalgo, William Israel (2019)
The compartment syndrome is a set of signs and symptoms that increase the pressure of the muscular compartments, these produce a reduction of the blood perfusion and a possible tissue ischemia. This condition is uncommon in our environment, but it can have very serious repercussions and is considered a surgical emergency. Although it does not show a prevalence for some type of sex or age group, it is more frequent in men than in women. The diagnosis of this pathology is given by measuring intracompartmental pressure, although it is under study if this is the most accurate method for its respective diagnosis, it must be accompanied by the patient's clinic where a characteristic symptom is pain. Fasciotomy is the first line of choice in the treatment of compartment syndrome, this is a procedure that decreases the pressure within the muscular fascia, which was the method applied in this clinical case.